Bahan Ajar IPA Berbasis Inkuiri Untuk Meningkatkan Literasi Sains - Itha Masithah; A. Wahab Jufri; Agus Ramdani (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this research is to develop appropriate inquiry-based science teaching materials to improve students' scientific literacy. This type of research includes research and development. The development research procedure carried out in teaching materials refers to the development steps of Dick and Carey, there are ten (10) stages. However, in this development research, it was only carried out up to stage nine (9) namely at the stage of implementing formative evaluation and revising the product. In addition to developing teaching materials, researchers also developed a syllabus, lesson plans, and evaluation instruments. This research only focuses on the priority of science teaching materials. The data collection technique used a validation questionnaire sheet which was assessed by product experts and media experts. The data analysis technique used Aiken's V. Based on the results of the validity analysis using the Aiken index and the reliability analysis using the agreed proportion, it is known that the inquiry-based science teaching materials developed have valid and reliable criteria.